2007
DOI: 10.1111/j.1365-2966.2007.12038.x
|View full text |Cite
|
Sign up to set email alerts
|

The evolution of the near-infrared galaxy luminosity function and colour bimodality up to z ≃ 2 from the UKIDSS Ultra Deep Survey Early Data Release

Abstract: We present new results on the cosmological evolution of the near‐infrared (near‐IR) galaxy luminosity function (LF), derived from the analysis of a new sample of ∼22 000 KAB≤ 22.5 galaxies selected over an area of 0.6 deg2 from the Early Data Release of the UKIDSS Ultra Deep Survey (UDS). Our study has exploited the multiwavelength coverage of the UDS field provided by the new UKIDSS WFCAM K‐ and J‐band imaging, the Subaru/XMM–Newton Deep Survey and the Spitzer Wide‐Area Infrared Extragalactic survey. The uniq… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
223
3

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 192 publications
(254 citation statements)
references
References 98 publications
28
223
3
Order By: Relevance
“…An optimal balance would be provided if we had chosen an [oii]λ3727 EW of about 11Å. This might slightly alter the comparison with Cirasuolo et al (2007) in Fig. 2 (b, c, see also below).…”
Section: Distant Galaxy Samplementioning
confidence: 99%
See 3 more Smart Citations
“…An optimal balance would be provided if we had chosen an [oii]λ3727 EW of about 11Å. This might slightly alter the comparison with Cirasuolo et al (2007) in Fig. 2 (b, c, see also below).…”
Section: Distant Galaxy Samplementioning
confidence: 99%
“…There is a relatively good correspondence between starforming and quiescent galaxies defined as above with blue and red galaxies, respectively. Figure 3 compares rest-frame (U − B) colors of galaxies in the distant sample with the limit applied by Cirasuolo et al (2007) to separate blue from red galaxies. It is, however, slightly imbalanced as there are more quiescent galaxies in the blue cloud than star-forming ones in the red cloud.…”
Section: Distant Galaxy Samplementioning
confidence: 99%
See 2 more Smart Citations
“…The latter also showed that the blue and red galaxy populations most probably had different evolutionary histories. Using a much larger sample, including ∼22 000 galaxies selected over an area of 0.6 deg 2 from the Early Data Release of the UKIDSS Ultra Deep Survey, Cirasuolo et al (2007) found that the colour bimodality disappears at z 1.5. With a large K-selected sample of more than 30 000 galaxies, Williams et al (2009) showed, that the bimodal distribution of star-forming and quiescent galaxies is still seen in a subsample of galaxies in the redshift range 1.5 < z < 2, but not above z = 2.…”
Section: Red Sequencementioning
confidence: 99%